ADVERSE EFFECTS OF RITLECITINIB IN ADULTS AND ADOLESCENTS WITH ALOPECIA AREATA: A LITERATURE REVIEW - Adrian Kruk; Dominika Walczak; Aleksandra Dorosz; Igor Gawłowski; Paweł Harbut; Weronika Ewa Nowak; Katarzyna Jakubowska; Aleksandra Miśta; Aleksander Białoń; Lidia Jurczenko (International Journal of Innovative Technologies in Social Science, 2025)
Alopecia areata is a chronic, autoimmune disease characterized by non-scarring hair loss on the scalp, face, or body and affects approximately 2% of the global population. The condition often results in significant psychological distress, particularly among adolescents. Ritlecitinib, a first-in-class, oral, selective dual inhibitor of Janus kinase 3 (JAK3) and tyrosine kinase expressed in hepatocellular carcinoma (TEC) family kinases, was recently approved for the treatment of severe AA in adults and adolescents aged 12 years and older. Background. Alopecia areata is characterized by non-scarring loss of scalp, face, or body hair. We investigated the efficacy and safety of ritlecitinib, an oral, selective dual JAK3/TEC family kinase inhibitor, in patients with alopecia areata. Material and methods. A comprehensive search of databases, including PubMed and Google Scholar, was conducted using the keywords mentioned below. Conclusions. The most commonly reported adverse effects of ritlecitinib in adults and adolescents with alopecia areata are headache, acne, and nasopharyngitis. These events are generally mild to moderate in severity and occur more frequently than with placebo. Other adverse effects observed include upper respiratory tract infections, urticaria, urinary tract infection, folliculitis, dizziness, and pyrexia. Laboratory abnormalities such as transient decreases in hemoglobin, neutrophil counts, platelets, and lymphocyte counts have been noted, but these changes tend to stabilize with continued treatment and are not typically associated with clinical sequelae. Serious adverse events - including malignancy, major adverse cardiovascular events, serious infections are rare, with no increased incidence compared to placebo in clinical trials up to 24 months. No deaths, opportunistic infections, or pulmonary embolisms have been reported in adult or adolescent populations during these studies. Discontinuation due to adverse events is infrequent, and the overall safety profile is considered acceptable for long-term use in patients aged 12 years and older. Real-world pharmacovigilance data corroborate these findings, showing that headache, increased blood creatine phosphokinase, urticaria, acne, and upper respiratory infections are the most frequently reported adverse events.